Akar Epistemik Hegemoni Politik Barat terhadap Nasionalisme di Timur Tengah - Mohammad Arifullah Ashaf (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2016)
Nationalism in the Middle East until now has not been able to create an atmosphere of peace in the life of the nation. This spawned the thesis that the nationalism that developed there really is not free from the influence of Western Europe to split the power of the Islamic world power. This paper is directed to probe the roots of Western European political epistemic hegemony on nationalism in the Middle East by applying the method of literature study. The hegemony of colonialism in the Middle East supported the rise of nationalism. Nationalism made Islam no longer used as the basis of unity of nations in the Middle East as is in the caliphate system. Nationalism is an imported product that is inseparable to modernization with the effect of disrupting the unity of the Islamic world, especially in countries of the Middle East.